A Stretchable Scaffold with Electrochemical Sensing for 3D Culture, Mechanical Loading, and Real‐Time Monitoring of Cells. Issue 13 (27th May 2021) - Qin, Yu; Hu, Xue‐Bo; Fan, Wen‐Ting; Yan, Jing; Cheng, Shi‐Bo; Liu, Yan‐Ling; Huang, Wei‐Hua
Abstract: In the field of three‐dimensional (3D) cell culture and tissue engineering, great advance focusing on functionalized materials and desirable culture systems has been made to mimic the natural environment of cells in vivo. Mechanical loading is one of the critical factors that affect cell/tissue behaviors and metabolic activities, but the reported models or detection methods offer little direct and real‐time information about mechanically induced cell responses. Herein, for the first time, a stretchable and multifunctional platform integrating 3D cell culture, mechanical loading, and electrochemical sensing is developed by immobilization of biomimetic peptide linked gold nanotubes on porous and elastic polydimethylsiloxane. The 3D scaffold demonstrates very good compatibility, excellent stretchability, and stable electrochemical sensing performance. This allows mimicking the articular cartilage and investigating its mechanotransduction by 3D culture, mechanical stretching of chondrocytes, and synchronously real‐time monitoring of stretch‐induced signaling molecules. The results disclose a previously unclear mechanotransduction pathway in chondrocytes that mechanical loading can rapidly activate nitric oxide signaling within seconds. This indicates the promising potential of the stretchable 3D sensing in exploring the mechanotransduction in 3D cellular systems and engineered tissues. Abstract : In this work, a stretchable three‐dimensional (3D) scaffold is developed with peptide linked gold nanotubes on porous and elastic polydimethylsiloxane, which integrates with functions of cell culture, mechanical stimulation, and powerful detection capability for the first time. The proposed scaffold is used for real‐time monitoring of stretch‐induced nitric oxide release from chondrocytes in exploring the mechanotransduction in 3D cellular systems.